Analisis Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Eupfin Elektronik Indonesia - Yohanes Sugiyanta; Nurul Azza Fitriani (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
Leadership style is the way the leader works and behaves in guiding his subordinates to do something. While work motivation is a work motivation for employees to work better and more effectively. Leadership style and work motivation will support and motivate employee performance for the better. Good employee performance will increase the productivity of the company. This study aims to determine the effect of leadership style and work motivation on employee performance at PT. Eupfin Electronics Indonesia . The sample in this study were 30 respondents. This study uses a partial test and multicollinearity test to find out how much influence the problem formulation has. From the results of the hypothesis test (t test) it shows that the leadership style variable has a Tcount value of 4,544 > 2.051 or a significant value of 0.000< 0.05. It can be concluded that leadership has a positive and significant effect on employee performance.While the work motivation variable is known to have a Tcount of 5,627>2.051 or a significant value of 0.000 <0.05. It can be concluded that work motivation has a positive and significant effect on employee performance. The results of the Statistical Test (F test) show that the calculated F value of 19.258 is greater than the Ftable value of 3.35 and it is also known that the significant level is 0.000 <0.05. This proves that leadership style and work motivation simultaneously affect employee performance.